A Settler Duoethnography About Allyship in an Era of Reconciliation - Burm, Sarah; Burleigh, Dawn (Alberta Journal of Educational Research, 2022)
As settler women, former teachers in First Nation communities, and scholars working in Indigenous education, we are responsible for engaging in the complexities of reconciliation through an allyship framework. In this article, we use duoethnography to critically engage in dialogue around the practice of allyship. In revisiting formative moments in our individual and collective teaching and research journey, we wade through some of the current tensions around solidarity work, problematizing the performative and binary approaches to allyship we see increasingly propagated across academic institutions and social groups. This critical dialogue illuminates how we might rethink becoming stronger collaborators with Indigenous people and engage others in exploring their allyship practice. Keywords: duoethnography, Indigenous education, allyship, reconciliation En tant que femmes colons, anciennes enseignantes dans des communautés des Premières nations et universitaires travaillant dans le domaine de l'éducation autochtone, nous avons la responsabilité de nous engager dans les complexités de la réconciliation à travers un cadre d'alliés. Dans cet article, nous utilisons la duoethnographie pour engager un dialogue critique sur la pratique d’agir comme allié. En revisitant les moments formateurs de notre parcours individuel et collectif d'enseignement et de recherche, nous nous frayons un chemin à travers certaines des tensions actuelles autour du travail de solidarité, en problématisant les approches performatives et binaires de l'allié que nous voyons de plus en plus propagées dans les institutions académiques et les groupes sociaux. Ce dialogue critique met en lumière la manière dont nous pourrions repenser à devenir des collaborateurs plus solides avec les peuples autochtones et inciter les autres à explorer leur pratique d'agir comme allié. Mots-clés : duoethnographie, éducation autochtone, allié, réconciliation